Dampak Sosialisasi Perpajakan Pada Efektivitas Implementasi Aplikasi Coretax, Kewajiban Perpajakan Terhadap Kepatuhan Wajib Pajak - Nugroho, Wawan Cahyo; Susila, Muktar Redy (Fakultas Ekonomi Prodi Akuntansi, 2026)
This study aims to test and analyze the effect of the effectiveness of the coretax application implementation and tax obligations on taxpayer compliance, by placing tax socialization as a moderating variable. Digital transformation through the coretax system is expected to reduce the tax gap, however, technical obstacles in the initial implementation phase indicate a gap between technological readiness and user adaptability. The theoretical basis used in this study is compliance theory to explain taxpayer compliance behavior towards fiscal authorities. The research method used is quantitative with data collection through questionnaires distributed to taxpayers. Data analysis was conducted using multiple linear regression analysis and Moderated Regression Analysis (MRA). The results show that the effectiveness of the coretax application implementation and tax obligations have a positive and significant influence on taxpayer compliance. This finding confirms that the modernization of the digital administration system and clarity of legal regulations are strong stimuli that encourage holistic compliance behavior. However, the moderation test shows that tax socialization is not proven to significantly moderate the effect of the effectiveness of the coretax application or the influence of tax obligations on taxpayer compliance. This indicates that when the tax information system has been designed independently and reliably, and legal regulations have binding legal force, taxpayers will immediately respond with compliance without relying on the intensity of external information stimuli. Keywords: Coretax Implementation, Tax Obligations, Taxpayer Compliance, Tax Socialization